Spin‐on‐dopant phosphorus diffusion in germanium thin films for near‐infrared detectors. Issue 1 (9th December 2013) - Sorianello, V.; De Iacovo, A.; Colace, L.; Fabbri, A.; Tortora, L.; Assanto, G.; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract Threading dislocations in germanium thin films on silicon introduce acceptor states in the germanium bandgap close to the valence band. Thus, highly defected germanium thin films spontaneously exhibit a p‐type behavior. Here we report on spin‐on‐dopant diffusion of phosphorus in thermally evaporated, highly defected germanium thin films. We demonstrate effective compensation of the acceptor states associated to dislocations by means of post‐growth doping. We discuss phosphorus diffusion in these highly defected films and pinpoint the benefits of spin‐on‐doping by realizing and testing near‐infrared photodiodes in evaporated Ge on Si, achieving high responsivities which compare well with those of state‐of‐the‐art Ge p‐i‐n photodiodes. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)